Education Status of the Santal Community in Northern Bangladesh: A Case Study (Teacher’s World: Journal of Education and Research, 2024)
Bangladesh is a land of cultural diversity, with several small ethnic groups living across the country, each with its own tradition and identity. The purpose of this study is to explore the educational status of the Santal community, one of the largest ethnic groups residing mainly in the northern part of Bangladesh. This study adopted a qualitative approach, using a case study as methodology. Data were collected through interviews, group discussions, and document analysis. The findings reveal that the educational status of the Santal community is characterized by poor enrolment, continuity and literacy rate. Despite receiving primary education, their attainment rate declines in the secondary, higher secondary, and university levels. In this regard, various socioeconomic factors contribute to the low educational attainment rate. The Santal children are unable to continue their studies mainly due to poverty. Furthermore, language barriers, future employment uncertainty, child marriage, gender discrimination, industrialization and cultural impediments are primarily responsible for low educational attainment. They are already fighting to make ends meet, so adding the expense of school to their list of concerns is excessive. Despite this, the majority of the young people, especially those who are currently pursuing education, acknowledge the value of education and aspire to improve their situation by reaching a high social position through educational attainment. It illustrates that the current generation is aware of the importance of education and is eager to continue their studies. As a case study, the results of this research demonstrate how ethnic groups have struggled to get education in Bangladesh and what steps should be taken to enhance education status, so adding to the existing literature on education and policy. The findings may also be useful for policymakers concerned in improving the educational status of ethnic groups, notably the Santal community.Teacher’s World: Journal of Education and Research, 49 (2),173-196